Basis functions for complex social decisions in dorsomedial frontal cortex - Marco K. Wittmann; Yongling Lin; Deng Pan; Moritz N. Braun; Cormac Dickson; Lisa Spiering; Shuyi Luo; Caroline Harbison; Ayat Abdurahman; Sorcha Hamilton; Nadira S. Faber; Nima Khalighinejad; et al. (Nature, 2025)
Abstract Navigating social environments is a fundamental challenge for the brain. It has been established that the brain solves this problem, in part, by representing social information in an agent-centric manner; knowledge about others’ abilities or attitudes is tagged to individuals such as ‘oneself’ or the ‘other’1–6. This intuitive approach has informed the understanding of key nodes in the social parts of the brain, the dorsomedial prefrontal cortex (dmPFC) and the anterior cingulate cortex (ACC)7–9. However, the patterns or combinations in which individuals might interact with one another is as important as the identities of the individuals. Here, in four studies using functional magnetic resonance imaging, behavioural experiments and a social group decision-making task, we show that the dmPFC and ACC represent the combinatorial possibilities for social interaction afforded by a given situation, and that they do so in a compressed format resembling the basis functions used in spatial, visual and motor domains10–12. The basis functions align with social interaction types, as opposed to individual identities. Our results indicate that there are deep analogies between abstract neural coding schemes in the visual and motor domain and the construction of our sense of social identity.